Association between physical intimate partner violence and postpartum contraceptive use in the United States-evidence from PRAMS 2016-2021. - Rashida-E Ijdi; Janine Barden-O'Fallon (PLoS ONE)
Objective Intimate Partner Violence (IPV) continues to be a major global public health concern, impacting physical and psychological well-being of individuals, including their reproductive and sexual health. The objective of this study is to examine the association between physical intimate partner violence and the utilization of contraception during the postpartum period in the United States. Method This study used data from the CDC's Pregnancy Risk Assessment Monitoring System (PRAMS) survey study phase 8, covering 2016-2021. The sample included 165,204 women reporting physical IPV during pregnancy or 12 months before their last pregnancy and their postpartum contraceptive use. Descriptive, bivariate, and logistic regressions were used to analyze the relationship between IPV and postpartum contraceptive use, adjusting for relevant factors and addressing sampling weights. Results The study found a 3.2% prevalence of physical IPV, with state variances ranging from 2.2% to 5.5%. Among women who experienced physical IPV, 91.0% used contraception, compared to 94.5% of those who did not experience physical IPV. Experiencing physical IPV significantly decreased the likelihood of using any postpartum contraceptive method by 42% (aOR: 0.58; 95% CI: 0.48-0.70) compared to those who did not experience physical IPV during the same period, after adjusting for covariates. Factors that increased the probability of using contraception during the postpartum period included women's higher educational attainment, being married or cohabitating, being employed anytime during pregnancy, and having an unintended last pregnancy. Conclusion This study highlights the significant association between physical IPV and reduced use of postpartum contraception in the United States. It calls for the integration of IPV considerations into public health policies and clinical initiatives to improve maternal well-being.